Development of the “SI KIMUL” Application (Oral and Dental Health System) for Elementary School Students - Arisya Pramesti Putri; Putri Rejeki; Desak Ayu Dhyana Nitha Dewi; Eko Sri Yuni Astuti (Ganesha Medicina, 2026)
Dental and oral health are essential components of overall health. In Bali Province, 46.5% of the population experiences oral and dental health problems, while Denpasar City ranks third among cities in Bali at 40.66%. This study aimed to develop the “Si Kimul” (Oral and Dental Health System) application as a health promotion medium for elementary school students and to evaluate its feasibility. The study was conducted at SD Negeri 12 Sesetan, Denpasar, Bali, using a Research and Development (R&D) approach consisting of eight stages. The sample consisted of 82 students from grades I–VI, selected using stratified random sampling. Data were collected using expert validation questionnaires, product trial questionnaires, and usability testing questionnaires, then analyzed quantitatively using Likert and Guttman scales. The results showed that material expert validation reached 92.25% and display expert validation reached 85.16%, both categorized as “Highly Feasible.” Product testing resulted in 88.86%, while usability testing reached 91.46%, also categorized as “Highly Feasible.” These findings indicate that the “Si Kimul” application is feasible as a digital health promotion medium to support oral and dental health education among elementary school students. Further development is recommended to improve cross-platform accessibility and broader implementation.